Politik Identitas dan Negara Bangsa di Riau - Erman; Muchid Albintani (Nakhoda: Jurnal Ilmu Pemerintahan, 2018)
Riau Vision 2020, regional regulations on Lembaga Adat Melayu[LAM] Riau, the issue of sons and non-sons of the region in regional head elections are the main characteristic of the ongoing revival of the Political Identity of the era of regional autonomy in Riau. The Rise of Identity Politics in Riau is considered to be at odds with the nation-state whose essence is recognizing diversity. The politics of identity in this context is considered to jeopardize the development of the diversity-based nation-state [nationalism]. This research aims, firstly, to address the Political Identity relationship with the nation-state in Riau in an effort to prevent local disintegration. Second, explaining the main obstacles to the Political Identity relationship with the nation-state in Riau in an effort to prevent local disintegration. The Political Approach to Identity and Nation- State is used as a theoretical framework. This study uses a qualitative approach with descriptive analysis method. Data is collected based on documents supported by interviews. After collecting the data analyzed qualitatively. The results of the study concluded, first, that the existence of the Riau 2020 vision, and the Riau Malay Customary Institution as a forum for empowerment of ‘Malays’ in the context of the Politics of Identity and State-nation, kept the potential for ethnicideological conflict. The concept of ‘Melayu’ in the vision impresses the sultry between Malay [ethnic] and Islam [ideology]. The vision is the consequence of local-minority hegemony. ‘Melayu’, structurally and constitutionally suggests that Melayu Malays ’control, even though there are minorities if they are accumulated with other ethnic groups. Second, the various obstacles that occur in the relationship between the Politics of Identity and State-nation are, [1] Malays are interpreted as hegemony in terms of relative deprivation. [2] Structural and cultural constraints have an effect on the relationship between the nation-state and the Politics of Identity [the existence of Riau LAM suggests more superiority and cultural domination. [3] Shifting issues in Political Idenitas, does not work linearly due to institutional-based personal interests. Practically this research provides an important reference for the relationship between LAM Riau and local governments that can prevent local disintegration. Academically, the relationship between the nation-state and the Politics of Identity can be constructed into a model and approach that can anticipate potential identity conflicts, especially in Riau.